115 Targeted use of right heart catheterisation in the management of shock: a case series. (6th June 2022) - Oldman, James; Graby, John; Mears, William; McKee, Ben; Kandan, Raveen; Augustine, Dan; Carson, Kevin
Abstract : Introduction: Circulatory shock is a life-threatening condition associated with in-hospital mortality rates as high as 45%. In some cases, there is a clear cause, when mechanical intervention such as revascularisation is often indicated. However, there is often a mixed picture with more than one underlying pathological mechanism. Right heart catheterisation (RHC) permits detailed evaluation of haemodynamics to enable better patient tailored therapy. ESC guidance suggests consideration of RHC in patients who, despite pharmacological treatment, have refractory shock or shock of unclear aetiology. Evidence from large registries is accumulating that RHC assessment in suspected cardiogenic shock is associated with favourable outcomes. To demonstrate the value of RHC assessment, ten patients with shock and a sub-optimal response to therapy or with suspected mixed pathology are reported. Methods: Retrospective analysis of ten patients who had RHC for shock of uncertain aetiology or not responsive to conventional therapy between June 2015 and 2020. Clinical course, therapy adjustment, survival to discharge, one month and one year were evaluated. Results: Eight patients were male and median age was 69 (IQR 8.5). Each patient had a mean of five comorbidities – most commonly - type 2 diabetes, ischaemic heart disease and left ventricular systolic dysfunction. Prior to RHC, five patients were in Society for Cardiovascular Angiography and Intervention (SCAI) stage C shock and five in stage D. Nine had ongoing infusions of vasopressors or inotropes, with five on two agents. RHC studies significantly changed management in 8/10 patients. Five patients had therapy changes in the catheter lab allowing real time monitoring of invasive haemodynamics. RHC evaluation led to a change in diagnosis in 4/10 patients and confirmed cardiogenic shock in 6/10 patients (with adjustment in ongoing therapy in 4 of these patients). Six patients survived to discharge and 4/10 to one year post RHC. The mean procedure duration was 47 minutes, and one patient had a retroperitoneal haematoma, which was successfully managed conservatively before being discharged, with no other complications recorded.SCAI shock stage, higher heart rate, lower mean aortic pressure and higher mean right atrial pressure were associated with mortality prior to discharge, one month and one year post RHC. Conclusions: In patients with shock of uncertain aetiology, or suboptimal response to standard therapy, RHC can provide important haemodynamic information to help optimise management.This observational data suggests that RHC assessment in these circumstances is an important tool to help assess and adjust medical therapy. It appears to be associated with favourable outcomes to discharge in a cohort of critically ill, comorbid patients at high-risk. Conflict of Interest: Nil